2015
DOI: 10.13080/z-a.2015.102.019
|View full text |Cite
|
Sign up to set email alerts
|

Control of annual broadleaf weeds by combinations of herbicides in sugar beet

Abstract: Sugar beet is a poor competitor to weeds. Weeds are a major constraint to sugar beet productivity. Field experiments were conducted at Institute of Agriculture, Lithuanian Research Centre for Agriculture and Forestry (55º23′ N, 23º51′ E) during the period 2010-2012 on a loamy Endocalcari-Epihypogleyic Cambisol (CMg-p-w-can) to determine the influence of tank-mixed herbicides phenmedipham + desmedipham + ethofumesate (136.5 + 106.5 + 168 g ha -1 a.i.) with chloridazon (624 g ha -1 a.i.), metamitron (700 g ha -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…Also, he added that the total broadleaf and total broadleaf and grassy weeds were significantly reduced by 54 and 91%, respectively, compared to untreated check in the second season. Our findings are consistent with those obtained by Attia et al (2011), Vasel et al (2012), Wujek et al (2012) and Deveikte et al (2015).…”
Section: Discussionsupporting
confidence: 94%
“…Also, he added that the total broadleaf and total broadleaf and grassy weeds were significantly reduced by 54 and 91%, respectively, compared to untreated check in the second season. Our findings are consistent with those obtained by Attia et al (2011), Vasel et al (2012), Wujek et al (2012) and Deveikte et al (2015).…”
Section: Discussionsupporting
confidence: 94%
“…The cultivar Punjab Masoor-2020 performed appreciably well with maximum SDW (5.02 g) while cultivar Punjab Masoor-2009 remained at lowest ranking with minimum SDW (4.62 g). In the current study, herbicide application and manual weed management lower weed growth, ensuring wider reliability of inputs and resources for lentil plants and, as an outcome, a substantial increase in shoot plant biomass.These findings are consistent with the findings of Wujek et al (2012) and Deveikte et al (2015), who found that herbicides lowered weed crop competition and leads to a significant increment in plant biomass.…”
Section: Shoot Dry Weight (G)supporting
confidence: 93%
“…All the herbicides and manual weeding reduced the weeds growth which in turn ensured the better availability of inputs and resources for plants and therefore, resulted in substantial increase in root fresh and dry biomass production. These results are comparable with outcomes of Wujek et al, (2012) and Deveikte et al,(2015) they also noted that herbicides reduced the weed crop competition and resulted in significant increase in the biomass production.…”
Section: Root Dry Weight (G)supporting
confidence: 90%
“…Effective weed control is particularly important for widely spaced crops, where postemergence dicotyledonous weed control is mainly based on the use of substances such as ethofumesate, phenmedipham, metamitron or chloridazon, clopyralid, and triflusulfuronmethyl [13]. Considering both external factors and herbicide formulations, selecting the right adjuvant is difficult, especially for a single-component adjuvant.…”
Section: Introductionmentioning
confidence: 99%